Intrarenal Renin Angiotensin System Imbalance During Postnatal Life Is Associated With Increased Microvascular Density in the Mature Kidney - Dalmasso, Carolina; Chade, Alejandro R.; Mendez, Mariela; Giani, Jorge F.; Bix, Gregory J.; Chen, Kuey C.; Loria, Analia S. (Frontiers in Physiology, 2020)
Environmental stress during early life is an important factor that affects the postnatal renal development. We have previously shown that male rats exposed to maternal separation (MatSep), a model of early life stress, are normotensive but display a sex-specific reduced renal function and exacerbated angiotensin II (AngII)-mediated vascular responses as adults. Since optimal AngII levels during postnatal life are required for normal maturation of the kidney, this study was designed to investigate both short- and long-term effect of MatSep on 1) the renal vascular architecture and function, 2) the intrarenal renin-angiotensin system (RAS) components status, and 3) the genome-wide expression of genes in isolated renal vasculature. Renal tissue and plasma were collected from male rats at different postnatal days (P) for intrarenal RAS components mRNA and protein expression measurements at P2, 6, 10, 14, 21 and 90 and microCT analysis at P21 and 90. Although with similar body weight and renal mass trajectories from P2 to P90, MatSep rats displayed decreased renal filtration capacity at P90, while increased microvascular density at both P21 and P90 (p<0.05). MatSep increased renal expression of renin, and angiotensin type 1 (AT1) and type 2 (AT2) receptors (p<0.05), but reduced ACE2 mRNA expression and activity from P2-14 compared to controls. However, intrarenal levels of AngII peptide were reduced (p<0.05) most likely due to the increased degradation to AngIII by aminopeptidase A. In isolated renal vasculature from neonates, Enriched Biological Pathways functional clusters (EBPfc) from genes changed by MatSep reported to modulate extracellular structure organization, inflammation, and pro-angiogenic transcription factors. Our data suggest that male neonates exposed to MatSep could display permanent changes in the renal microvascular architecture in response to intrarenal RAS imbalance in the context of the atypical upregulation of angiogenic factors.